2018
DOI: 10.1186/s12884-018-1915-x
|View full text |Cite
|
Sign up to set email alerts
|

A village-matched evaluation of providing a local supplemental food during pregnancy in rural Bangladesh: a preliminary study

Abstract: BackgroundPrenatal balanced protein energy supplementation consumed by undernourished women improves mid-upper arm circumference in early infancy. This study aimed to identify whether locally produced maternal food-based supplementation improved anthropometric measures at birth and early infancy.MethodsA village-matched evaluation, applying principles of a cluster randomised controlled trial, of a locally produced supplemental food to 87 undernourished pregnant women. 12 villages (intervention: n = 8; control:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…No significant difference was observed in other maternal and infant outcomes. 26 The study from Bangalore did not observe any significant difference in GWG, birthweight, birth length, or gestational age in 12 underweight pregnant women (BMI <18.5) who were provided a daily food supplement. 27…”
Section: Bep Supplementationmentioning
confidence: 80%
“…No significant difference was observed in other maternal and infant outcomes. 26 The study from Bangalore did not observe any significant difference in GWG, birthweight, birth length, or gestational age in 12 underweight pregnant women (BMI <18.5) who were provided a daily food supplement. 27…”
Section: Bep Supplementationmentioning
confidence: 80%
“…Of all the 31 studies included in the review, only 22 have at least one outcome associated with delivery mechanisms; the study characteristics of all the 31 papers are summarized in Table 1 and Table 2 [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. A total of 22 studies were ultimately included in this review for narrative synthesis [ 17 , 18 , 20 , 21 , 22 , 23 , 24 , 25 , 27 , 28 , 29 , 32 , 33 , 34 , 36 , 37 , 39 , 40 , 42 , 43 ...…”
Section: Resultsmentioning
confidence: 99%
“…In Nepal, the provision of 10 kg per month of a fortified BEP supplement of wheat-soya blended flour with 10% added sugar, called super cereal, delivered by community health workers, along with the participatory learning and action approach, significantly improved the birth weight of newborns and equity in energy allocation among pregnant women [ 37 , 40 ]. Similarly, in Bangladesh, a locally produced food-based BEP supplementation for undernourished pregnant women delivered along with nutrition education and counselling and regularly monitored by community nutrition volunteers either at the designated center in the community or through home visits showed a 98% compliance rate, with almost all women consuming the full supplement daily [ 43 ]. However, evaluation of supplementary food programs delivered in India through the Integrated Child Development Service Scheme by Anganwadi workers reported that only 20.5% of women received supplementary food during their pregnancies due to a weak procurement system and poor quality of food products [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In some cases, additional energy and nutrients lead to gains in perinatal outcomes across the study sample (eg, Huynh, Tran, Nguyen, Berde, & Low, ). In others, they do not (eg, Mantaring et al, ; Stevens et al, ). Most recent studies in diverse populations, however, point to the importance of maternal and ecological characteristics in mediating the impact of supplementation.…”
Section: Prenatal Supplementation Studies: Contingent Outcomesmentioning
confidence: 99%